Pengaruh Profesionalitas Dan Motivasi Kerja Terhadap Produktivitas Kerja Pegawai Dinas Pekerjaan Umum Dan Penataan Ruang Palembang - arizona, rio; mulyani, agus; heryati, heryati (Peneliti.net, 2023)
The purpose of this study is to determine the influence of professionalism and job motivation on the work productivity of employees of the Public Works and Spatial Planning Agency of Palembang. This research uses an associative method. The population in this study consists of all employees of the Palembang Public Works and Spatial Planning Agency (PUPR), totaling 105 people, including 64 civil servants and 41 honorary employees. The sample in this study consists of 64 employees of the Palembang Public Works and Spatial Planning Agency (PUPR). The data collection techniques used in this study are questionnaires and documentation. Based on the research findings, it is concluded that there is a significant influence of professionalism and job motivation simultaneously on the work productivity of employees of the Palembang Public Works and Spatial Planning Agency (PUPR). This means that professionalism and job motivation can affect employee work productivity.